Kolaborasi Model Pentahelix dalam Pengembangan Kota Yogyakarta sebagai Kota Kreatif - Yumna, Auliaturrahma; Sahita, Astrie Purnamaning; Budi, Gian Mahardika Setia; Kamila, Qotrun Nada (REKSABUMI, 2025)
Yogyakarta is known for its rich cultural heritage and high level of creativity, which has led to efforts to develop the city as a creative city. This study explores actor collaboration within the framework of the pentahelix model in driving Yogyakarta’s transformation into a sustainable creative city. This approach emphasizes the importance of synergy among these elements in building an inclusive, innovative, and locally rooted creative ecosystem. Using a qualitative method by identifying secondary data, the study highlights forms of collaboration such as the development of creative zones, implementation of policies and infrastructure, and community involvement in cultural policy formulation. The findings show that active community participation and bureaucratic flexibility are key factors in the success of collaboration. However, challenges remain, such as communication gaps between actors, unequal access to resources, and the lack of a long-term coordination system. The most significant challenge lies with business actors, who show limited interest in the existing sub-sectors of Yogyakarta’s creative city. This research recommends strengthening cross-sector collaborative platforms, enhancing the capacity of creative communities, and the need for policies that are responsive to the dynamics of the creative industry. Collaboration based on the pentahelix model proves to be a strategic approach in realizing Yogyakarta as a creative city that not only fosters economic growth but also preserves its local cultural identity.